Bibliometric Analysis of The Development Map and Research Directions of Blanded Learning on Scopus Database (2013-2024) - Fitriana, Tri Anggraini; Maksum, Muh. Nur Rochim; Salim, Hakimuddin; Andhim, Muk. (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This inquire about points to decide the advancement and heading of Blanded Learning inquire about in distributions recorded by Scopus. This inquire about employments bibliometric investigation strategies to investigate all distributions ordered within the Scopus database on Blanded Learning from 2013 to 2024. Information analyzed utilizing Exceed expectations and R/R-Studio. VOSviewer is utilized to perform visual investigation of the concurrent event of watchwords and archive cites. The creator found 2,357 distributions that coordinated the work, subject and criteria indicated. The comes about of this investigate appear an yearly development rate of 355 with the foremost distributions on Blanded Learning in 2022. United States is the nation that contributes the foremost distributions with connection from Brigham Youthful Graham, CR being the foremost profitable author on the topic of Blanded Learning. The bibliometric analysis carried out was constrained to Scopus information. Other national and universal databases were not taken into consideration in this think about. This think about presents a brief diagram of the writing open to analysts and gives proposals for future investigate.